Trójkąt Weimarski po rozszerzeniu UE – niewykorzystany instrument polskiej polityki zagranicznej? - Wyligała, Helena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
Following the enlargement of the European Union, Poland was expected to become a significant creator of European policy in the Community, and an equal partner to Germany and France. This was supposed to translate into intensified activity by Poland in the Weimar Triangle. New Weimar projects were expected to provide a new core for the EU, thus sparking a European integration process. However, over the five years of Poland’s membership in the EU, the inter-governmental Weimar initiative has diminished in importance, despite diplomats’ assurances of its useful character. On the other hand, trilateral ventures in social, cultural and regional areas have blossomed. The paper analyzes external and internal factors affecting the activity of the Weimar Triangle. The unused mechanisms of the Triangle and potential cooperation fields are discussed. This is done against the background of considerations on the change in priorities of Polish foreign policy after 2004, and Berlin and Paris’s search for strategic partners in an enlarged EU. The conclusion presents the answer to the question of whether the Weimar Triangle can still be included in the arsenal of instruments of Polish diplomacy, and what prerequisites might herald its revival in the near future.